TUNTUTAN KEADILAN PERSPEKTIF HUKUM ISLAM - Zulkifli Zulkifli (JURIS (Jurnal Ilmiah Syariah), 2018)
The justice is viewed from any perspectives and aspects, it means the justice must be positioned as well as possible depends on the situation and time (when and where). In law empowerment all people have the same position and they should get their human right. Method which is used in this study was library research. There is a phenomena where the human right is not found in every human life, but actually it must reach all factors of the human life which having different and balanced. In deciding the justice for human life, it must be as proportional as possible eventhough the right is not always reaching the same position.